Comparison of Inhalational Vital Capacity Induction with Sevoflurane to Intravenous Induction with Propofol - Adhikari, Krishna Murari; Lakhe, Gajal (Nepal Journal of Medical Sciences, 2020)
Introduction: Intravenous propofol is commonly used for induction of general anesthesia because it is smooth and rapid. Inhalational induction method is used in limited situations like absence of venous access and difficult intubation. Sevoflurane also produces rapid induction comparable to propofol. We conducted this study to compare induction time and quality of sevoflurane with that of propofol. Methods:Total 102 patient undergoing elective laparoscopic surgery were divided into Group S and Group P with 51 patient in each group. In group S patient were induced with Sevoflurane 8% via vital capacity induction method. In group P, patients were induced with injection propofol 1% with titrating dose. Induction time, hemodynamic changes and complications during induction, patient satisfaction and cost of induction were compared. Results: Induction was rapid in Group S (53.33±17.29s) compared to Group P (72.27±25.15s) (p=0.01). The heart rate and mean arterial pressure were stable in both groups upto one minute after induction. Hypotension occurred more in Group P than in Group S (47.05%vs.37.25%).Cough (9.80 %vs.5.88%) and excessive secretions (5.88%vs.0%) were common in Group S while apnea (3.92%vs5.88%) and involuntary movements(17.64% vs. 27.45%) were common in Group P. Patient satisfaction score was high in both the groups. Cost of induction was cheaper in Group S compared with Group P (1.6±0.54 vs.1.9±0.43). Conclusions: Vital capacity induction with 8% sevoflurane has rapid induction and cheaper as compared to intravenous induction with propofol in a titrating dose. Hemodynamic changes and complications were comparable in both the groups.